2023
DOI: 10.3390/molecules28020803
|View full text |Cite
|
Sign up to set email alerts
|

Sinomenine Hydrochloride Can Ameliorate Benign Prostatic Hyperplasia by Lowering the 5α-Reductase 2 Level and Regulating the Balance between the Proliferation and Apoptosis of Cells

Abstract: Benign prostatic hyperplasia (BPH) is a chronic disease that affects the quality of life of older males. Sinomenine hydrochloride (SIN) is the major bioactive alkaloid isolated from the roots of the traditional Chinese medicinal plant Sinomenium acutum Rehderett Wilson. We wondered if the SIN administration exerted a regulatory effect on BPH and its potential mechanism of action. Mice with testosterone propionate-induced BPH subjected to bilateral orchiectomy were employed for in vivo experiments. A human BPH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…SIN therapy significantly reduced protein expression of Bcl-2 and PCNA in the PG tissues of mice with TP-induced BPH in vivo, indicating that SIN treatment alleviated BPH via the apoptotic pathway, which was consistent with in vitro data. These findings suggest that SIN treatment may improve BPH via the apoptotic pathway [32,33]. Inflammation is another mechanism for the development of BPH, which is also an important clue.…”
Section: Figure 7 A-liver Without Histological Alterations (40x) B-li...mentioning
confidence: 74%
“…SIN therapy significantly reduced protein expression of Bcl-2 and PCNA in the PG tissues of mice with TP-induced BPH in vivo, indicating that SIN treatment alleviated BPH via the apoptotic pathway, which was consistent with in vitro data. These findings suggest that SIN treatment may improve BPH via the apoptotic pathway [32,33]. Inflammation is another mechanism for the development of BPH, which is also an important clue.…”
Section: Figure 7 A-liver Without Histological Alterations (40x) B-li...mentioning
confidence: 74%
“…M. S. Fan et al reported that SH (25, 50, and 100 µM) inhibited BcL-2 and increased Bax protein expression, thereby suppressing the proliferation of BPH-1 cells. SH at doses of 0.5, 1, and 2 mg/kg decreased steroid 5-alpha reductase 2 (SRD5A2), PCNA, BcL-2, and MMP-2 [ 222 ]. The various other bioactivities of SIN are detailed in Table 15 .…”
Section: Other Activities Of Sinmentioning
confidence: 99%